Comparative study of the molecular mechanism of action of the synthetic progestins, Medroxyprogesterone acetate and Norethisterone acetate - Africander, Donita Jean (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Biochemistry))--University of Stellenbosch, 2010.